Domain of Euler Mean in the Space of Absolutely $p$-Summable Double Sequences with $0< p (Analysis in Theory and Applications, 2018)
In this study, as the domain of four dimensional Euler mean $E(r,s)$ of orders $r$, $s$ in the space $\mathcal{L}_p$ for $0